Integrating Remote Labs into Personal Learning Environments - Experiential Learning with Tele-operated Experiments and E-portfolios - Terkowsky, Claudius; May, Dominik; Haertel, Tobias; Pleul, Christian (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The use of laboratories in Higher Engineering Education is an adequate opportunity to implement forms of experiential learning like problem-based or research-based learning into manufacturing technology. The introduction of remote laboratories gives students the opportunity to do self-directed research and by that having their own and unique learning experiences. Recently finished research projects, e.g. the PeTEX project, implemented research-based learning by deploying real laboratory equipment without being physically in the laboratory but by accessing it via the Internet. One essential question in this context is on the one hand how the student can document his/her own learning processes and how the teacher can guide the student through these processes on the other hand. The proposed solution in this paper is a personal learning environment that integrates a remote lab and an e-portfolio system. E-portfolios enable the student to individually and collectively document and reflect what he/she has been doing and to share his/her outcomes with others. The paper outlines the important role that e-portfolios can play as personal learning environments to experience remote laboratory work and to foster creative attitudes.